Influence of Lentinus edodes and Agaricus blazei extracts on the prevention of oxidation and retention of tocopherols in soybean oil in an accelerated storage test - Silva, Ana Carolina da [UNESP]; Jorge, Neuza [UNESP] (Springer, 2014)
This study aimed to evaluate the influence of the methanol extracts of mushrooms Lentinus edodes and Agaricus blazei on the retention of tocopherols in soybean oil, when subjected to an accelerated storage test. The following treatments were subjected to an accelerated storage test in an oven at 60 A degrees C for 15 days: Control (soybean oil without antioxidants), TBHQ (soybean oil + 100 mg/kg of TBHQ), BHT (soybean oil + 100 mg/kg of BHT), L. edodes (soybean oil + 3,500 mg/kg of L. edodes extract) and A. blazei (soybean oil + 3,500 mg/kg of A. blazei extract). The samples were analyzed for tocopherols naturally present in soybean oil and mass gain. The results showed, the time required to reach a 0.5% increase in mass was 13 days for TBHQ and 15 days for A. blazei. The content of tocopherols for TBHQ was 457.50 mg/kg and the A. blazei, 477.20 mg/kg.
Keywords: Mushroom; Antioxidants; Mass gain; Tocopherols